A arte e os discursos intolerantes que a cercam (Palíndromo, 2017)
In this article the objective is to analyze discourses conveyed in the media that propose censors hip to the Arts, toreflectand examine how the se manifestations expose values and ideologies that spread intolerance. With reference in Adorno the analytical methodology for the study of the texts is based on the proposition of Barros (2011) for the examination of the discursive construction of in tolerant speeches. What is intended is the contribution to this debate through language studies, enabling the art teacher to intervene critically based on arguments that expose the intolerance that these discourses carry.
Keywords: art and society; intolerant speeches; art analysis